Word Guess Bouquet for Junior High School Vocabulary Learning: Permainan Tebak Kata untuk Pembelajaran Kosakata Siswa SMP - Rochmawati, Fivi; Fediyanto, Niko (Indonesian Journal of Education Methods Development, 2026)
General Background Vocabulary mastery is a fundamental component of English language learning, supporting learners’ abilities in reading, writing, listening, and speaking. Specific Background Junior high school students often experience difficulties in acquiring and retaining verbs and nouns when instruction relies on conventional memorization-based approaches. Knowledge Gap Existing studies emphasize interactive media, yet limited attention has been given to tangible, game-based visual tools that integrate categorization and contextual use of vocabulary. Aims This study aims to examine the use of Word-Guess Bouquet as an interactive medium for learning English verbs and nouns among junior high school students. Results The findings indicate that the implementation of Word-Guess Bouquet supports students’ vocabulary mastery by encouraging active participation, collaborative learning, and contextual application of words. Students demonstrated improved ability to distinguish and use verbs and nouns during learning activities. Novelty This study introduces a bouquet-shaped visual learning medium that combines guessing, classification, and contextual sentence use within a game-based format. Implications The results suggest that integrating creative, student-centered media such as Word-Guess Bouquet can support vocabulary instruction in EFL classrooms and provide practical insights for teachers seeking interactive alternatives to traditional vocabulary teaching. Keywords : Word-Guess Bouquet, Vocabulary Learning, Verbs and Nouns, Junior High School, Interactive Media Key Findings Highlights Interactive bouquet-based media supported students’ active engagement in vocabulary learning Learners demonstrated clearer differentiation between verbs and nouns during activities Game-oriented visual tools encouraged collaborative and low-anxiety classroom interaction